Resonance enhanced multiphoton ionization detection of aromatics formation in fuel-rich flames - Kasper, Tina; Hansen, Nils (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Human Factors in der integrierten Produktentwicklung - Gräßler, Iris; Roesmann, Daniel; Pottebaum, Jens (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
In der zukünftigen Produktion werden der Aufbau und die Entwicklung der Fähigkeiten der Mitarbeiter:innen ein entscheidender Wettbewerbsvorteil von Unternehmen. In menschenzentrierten Montagesystemen passen sich die Mitarbeiter:innen auf der Grundlage von Lernprozessen an neue und sich ändernde Aufgaben an. Dazu muss der Bezug zu den Fähigkeiten der Mitarbeiter:innen im Zuge der integrierten Produkt-und Prozessentwicklung vorgesehen werden. Daher wurde eine Methodik entwickelt, die diese Fähigkeiten explizit abbildet und sie sowohl in der Entwicklung als auch in der kurzfristigen Personaleinsatzplanung bei der Aufgabenzuordnung berücksichtigt. Zur Anwendung wurde die Methodik prototypisch in einem Software-Werkzeug umgesetzt und in Kombination mit einer diskreten ereignisorientierten Simulation erprobt.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Emerging disciplinary voices - Stock, Ingrid; Karsten, Andrea; Eik-Nes, Nancy Lea (Sakprosa)
While referencing is an important feature of academic writing, many students struggle with using sources. This struggle seems to be due, in part, to the tension students experience when advised to cite sources (i.e., others’ voices) on the one hand, and to demonstrate their own disciplinary voice on the other hand. The aim of this article is to contribute to the understanding of source use, presenting a figure that illustrates gradients of students’ engagement with sources in various sections of their bachelor’s theses. Based on Bakhtin’s idea that a writer’s voice gradually emerges out of others’ words, and the terms knowledge telling and knowledge transforming, we developed a continuum that might help to understand the complexity of source use. We arrived at this continuum through the qualitative exploration of students’ use of sources in 15 bachelor’s theses from the humanities in one Norwegian university. In this article, we illustrate the continuum through extracts from the students’ theses, showing how issues of voice are intertwined with students’ engagement with sources. We propose that understanding the various functions of sources as they are typically used in the disciplines will help students to develop and demonstrate their disciplinary voices. Moreover, the continuum provides a foundation for fruitful discussions of writing practices that raise critical awareness about implicit expectations concerning source use and issues of voice in academic writing.
Keywords: Automotive Engineering

Christine Schwanecke: A Narratology of Drama: Dramatic Storytelling in Theory, History, and Culture from the Renaissance to the Twenty-First Century - Tönnies, Merle

"ProGRess" - Erste Evaluationsergebnisse eines Anti-Prokrastinationstrainings auf Basis des Zürcher Ressourcen Modells (ZRM). - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Reduce procrastination to improve students' health - First analyses of an intervention study. - Schneider, Tamara; Klingsieck, Katrin B.

Vorausschau und Technologieplanung. 17. Symposium für Vorausschau und Technologieplanung - Dumitrescu, Roman; Hölzle, K.

Poster: Circumventing the GFW with TLS Record Fragmentation - Niere, Niklas; Hebrok, Sven Niclas; Somorovsky, Juraj; Merget, Robert (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)
State actors around the world censor the HTTPS protocol to block access to certain websites. While many circumvention strategies utilize the TCP layer only little emphasis has been placed on the analysis of TLS-a complex protocol and integral building block of HTTPS. In contrast to the TCP layer, circumvention methods on the TLS layer do not require root privileges since TLS operates on the application layer. With this proposal, we want to motivate a deeper analysis of TLS in regard to censorship circumvention techniques. To prove the existence of such techniques, we present TLS record fragmentation as a novel circumvention technique and circumvent the Great Firewall of China (GFW) using this technique. We hope that our research fosters collaboration between censorship and TLS researchers.

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Rezension zu D. Pokitsch: Wer spricht? Sprachbezogene Subjektivierungsprozesse in der Schule der Migrationsgesellschaft - Büttner, Denise (Zeitschrift für Deutsch im Kontext von Mehrsprachigkeit (ZDKM))

ProDaZ Online-Tool Philosophie - Büttner, Denise; Jost, Leif Marvin

Error analysis for the numerical approximation of the harmonic map heat flow with nodal constraints - Bartels, Sören; Kovács, Balázs; Wang, Zhangxian (IMA Journal of Numerical Analysis)
Abstract An error estimate for a canonical discretization of the harmonic map heat flow into spheres is derived. The numerical scheme uses standard finite elements with a nodal treatment of linearized unit-length constraints. The analysis is based on elementary approximation results and only uses the discrete weak formulation.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Error analysis of BDF 1-6 time-stepping methods for the transient Stokes problem: velocity and pressure estimates - Contri, Alessandro; Kovács, Balázs; Massing, André (arXiv)
We present a new stability and error analysis of fully discrete approximation schemes for the transient Stokes equation. For the spatial discretization, we consider a wide class of Galerkin finite element methods which includes both inf-sup stable spaces and symmetric pressure stabilized formulations. We extend the results from Burman and Fernández [\textit{SIAM J. Numer. Anal.}, 47 (2009), pp. 409-439] and provide a unified theoretical analysis of backward difference formulae (BDF methods) of order 1 to 6. The main novelty of our approach lies in the use of Dahlquist's G-stability concept together with multiplier techniques introduced by Nevannlina-Odeh and recently by Akrivis et al. [\textit{SIAM J. Numer. Anal.}, 59 (2021), pp. 2449-2472] to derive optimal stability and error estimates for both the velocity and the pressure. When combined with a method dependent Ritz projection for the initial data, unconditional stability can be shown while for arbitrary interpolation, pressure stability is subordinate to the fulfillment of a mild inverse CFL-type condition between space and time discretizations.

Editorial: Remote @ Distance - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Antimicrobial Brushes on Titanium via “Grafting to” Using Phosphonic Acid/Pyridinium Containing Block Copolymers - Methling, Rafael; Dückmann, Oliver; Simon, Frank; Wolf‐Brandstetter, Cornelia; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract Coating medical implants with antibacterial polymers may prevent postoperative infections which are a common issue for conventional titanium implants and can even lead to implant failure. Easily applicable diblock copolymers are presented that form polymer brushes via “grafting to” mechanism on titanium and equip the modified material with antibacterial properties. The polymers carry quaternized pyridinium units to combat bacteria and phosphonic acid groups which allow the linear chains to be anchored to metal surfaces in a convenient coating process. The polymers are synthesized via reversible‐addition‐fragmentation‐chain‐transfer (RAFT) polymerization and postmodifications and are characterized using NMR spectroscopy and SEC. Low grafting densities are a major drawback of the “grafting to” approach compared to “grafting from”. Thus, the number of phosphonic acid groups in the anchor block are varied to investigate and optimize the surface binding. Modified titanium surfaces are examined regarding their composition, wetting behavior, streaming potential, and coating stability. Evaluation of the antimicrobial properties revealed reduced bacterial adhesion and biofilm formation for certain polymers, albeit the cell biocompatibility against human gingival fibroblasts is also impaired. The presented findings show the potential of easy‐to‐apply polymer coatings and aid in designing next‐generation implant surface modifications.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; General Chemical Engineering

Coworking - Krause, Ina (Arbeit)
Zusammenfassung Der Beitrag beschäftigt sich mit dem Konzept Coworking und arbeitet auf Basis eigener empirischer Daten heraus, wie dieses Konzept im Zuge seiner wachsenden Verbreitung und der Etablierung von Coworking-Spaces als ‚dritten Orten der Arbeit‘ Legitimität für neue Gestaltungsideen und Wertvorstellungen von Büroarbeit generiert. Coworking-Spaces werden dabei als ‚dritte Orte‘ definiert, die dem Raumkonzept der Schaffung einer flexibel anpassbaren und Kreativität fördernden Arbeitsumgebung für Büroarbeiter:innen folgen. Das Geschäftskonzept Coworking-Space wird inzwischen aber auch als alternatives Organisationsmodell von Arbeit wahrgenommen. Dem Beitrag liegt das Forschungsinteresse zugrunde zu erkunden, wie und in welchen Variationen das Konzept Coworking in Büroarbeitsorganisationen, die sich selbst als Coworking-Space bezeichnen, adaptiert und praktisch umgesetzt wird. Nachgezeichnet wird, inwiefern Coworking als alternatives Gestaltungsmodell oder, im Sinne von Meyer und Rowan, Rationalisierungskonzept der Organisation von Arbeit Elemente eines neuen Normalitätsverständnisses von Büroarbeit generiert, welches über Betreiber:innen von Coworking-Spaces und Coworker:innen inzwischen in die Breite der Arbeitsgesellschaft getragen wird.
Keywords: Industrial and Manufacturing Engineering

Polymeric Networks Containing Amine Derivatives as Organocatalysts for Knoevenagel Reaction within Continuously Driven Microfluidic Reactors - Killi, Naresh; Bartenbach, Julian; Kuckling, Dirk (Gels)
The Knoevenagel reaction is a classic reaction in organic chemistry for the formation of C-C bonds. In this study, various catalytic monomers for Knoevenagel reactions were synthesized and polymerized via photolithography to form polymeric gel dots with a composition of 90% catalyst, 9% gelling agent and 1% crosslinker. Furthermore, these gel dots were inserted into a microfluidic reactor (MFR) and the conversion of the reaction using gel dots as catalysts in the MFR for 8 h at room temperature was studied. The gel dots containing primary amines showed a better conversion of about 83–90% with aliphatic aldehyde and 86–100% with aromatic aldehyde, compared to the tertiary amines (52–59% with aliphatic aldehyde and 77–93% with aromatic aldehydes) which resembles the reactivity of the amines. Moreover, the addition of polar solvent (water) in the reaction mixture and the swelling properties of the gel dots by altering the polymer backbone showed a significant enhancement in the conversion of the reaction, due to the increased accessibility of the catalytic sites in the polymeric network. These results suggested the primary-amine-based catalysts facilitate better conversion compared to tertiary amines and the reaction solvent had a significant influence on organocatalysis to improve the efficiency of MFR.
Keywords: Knoevenagel reaction; organocatalysis; polymeric gel dots; microfluidic reactions; polymeric networks

Im Osten nichts Neues? Über (un)bekannte Akteure in der regionalen Weiterbildungslandschaft. - Krause, Ina; Biess, Anne; Bohlinger, Sandra (bwp@ Berufs- und Wirtschaftspädagogik – online)

Entkoppelte Arbeitswelten - Krause, Ina
Die Strukturen der industriell geprägten Arbeitsgesellschaft werden durch den zunehmenden Einsatz automatisierter und digitaler Technologien sowie den Ausbau der Infrastruktur des Internets maßgeblich verändert. Gleichzeitig lässt sich eine intensive Flexibilisierung vertrauter Strukturen betriebszentrierter Organisationsformen von Beschäftigung beobachten. Ina Krause beschreibt einzelne Dynamiken auf der gesellschaftlichen Mesoebene und trägt damit zur Debatte über die nachhaltige Gestaltung der digitalen und virtuellen Arbeitsgesellschaft in Deutschland bei.